Determinants of student loyalty from service quality through their satisfaction in Bphram education – A proposed model - Nghia, Nguyen Thanh; Singh, Harwindar; Thuy Khanh, Thai Hong (Technium Social Sciences Journal, 2021)
Educational service is recognized as an emerging term in academic sectors. In global perspective, higher education is affirmed as a business and students, or parents and other related bodies are customers of universities. For their sustainable development, they insist on development and enhancement of their service quality by improving student satisfaction. Significantly, research of factors affecting student loyalty from service quality with the intermediating role of customer satisfaction of Bpharm education institutions Vietnam is really limited. Hence, this study is to propose a theoretical model on that matter for private universities located in Ho Chi Minh city in special and in Vietnam in general. To achieve that objective, the study uses mainly qualitative approach with the techniques of the systematic review, the meta-analysis, and the expert consultation with the data from different sources including Google Scholar, Scopus, Web of Science (WoS), EBSCO, Cengage and Springer, etc. From which, 145 publications have been found eligible for this study. Also, the study contributes to the knowledge of educational quality management and requires empirical studies to confirm whether the proposed framework exists or is adjusted for practical implementation.